Branding higher education: an exploration of the role of internal branding on middle management in a university rebrand - Paul Clark; Chris Chapleo; Kati Suomi (Springer, 2022)
Although research on branding in higher education has grown, a specific focus on internal branding in this sector is still scarce. Brand support by mid-level administrative staff and deans is a key element in internal branding of a university. This study explores the extent to which internal branding contributes to this group’s understanding of and engagement with a public institution’s rebranding campaign. It identifies challenges and practice insights for practice for internal branding activities when engaging these internal stakeholders, linking to wider brand management theory and practice. A qualitative case study approach was employed to understand the effectiveness of internal branding holistically, and in context. In 2016, nineteen depth interviews were conducted with a range of midlevel administrators and deans including those at the student union, regional campuses, directors of departments, and deans of faculties and schools at a large Canadian university. The data was analysed using Nvivo qualitative data analysis software. On the basis of the results, it is apparent that internal branding has a valuable role in relation to higher education brand management strategy. Results offer a holistic view of the rebranding process, and explore understanding of and engagement with the rebranding campaign. This paper addresses a gap in the public sector brand management literature and demonstrates theoretical and practical implications for improved understanding and brand management strategy.